Study on Implementation of School Health Program (UKS) - Elisabeth Sandria Lisu; Afrona E. L. Takaeb; Helga J. N. Ndun (Universitas Nusa Cendana, 2022)
School Health Efforts are an important prospect in efforts to prevent disease and improve children's health. This study aims to describe the implementation of UKS, namely the implementation of the three main UKS programs, the role of teachers, and infrastructure. This research is qualitative research with a phenomenological approach. Data was collected through in-depth interviews and documentation with 10 informants. The results showed that the types of UKS activities included health education, health services, and fostering a healthy school environment. UKS activities are not routinely carried out and experience problems in their implementation. The teacher's role in UKS activities includes providing information, assessing, examining, and guiding students to clean independently. Regarding the currently available infrastructure, it is still limited and does not meet the minimum level of UKS services improvement of UKS infrastructure facilities, improvement of teacher knowledge, and skills in UKS management is very much needed.